Evaluation of Fe and Mn movement in soil and potential of castor bean (Ricinus communis L.) for Fe and Mn phytoremediation - Mariam Mohammed Khalifa ,Abdalsalam Mohammed Almathnani , Aishah Ramadan Mohamed (Journal of Pure & Applied Sciences, 2019)
This study presents the assessment of movement the Fe and Mn in soils, and and potential of castor bean (Ricinus communis L.) for Fe and Mn phytoremediation. A pots experiment was conducted to understand the potential of Ricinus communis L.  in Fe and Mn uptake from the sandy soil and sandy clay soil irrigated with different concentrations of Fe and Mn. Results obtained during this study indicated that The highest concentrations of Fe and Mn were found in plant and soil irrigated with highest levels of Mn and Fe (0.104  mg/kg in sandy soil) and (0.1013 mg/kg in sandy clay soil) . Phytoremediation alternative solution can be used for heavy metal remediation process because of its advantages as a cost-effective, efficient, and eco-friendly technology based on the use of metal-accumulating plants. The results showed that Ricinus communis L was tolerant plant to the studied mixed contaminants (Mn and Fe). Furthermore, castor bean r was able to remove metals from the studied soils, and it can identified as suitable for phytoremediation of metal-contaminated soil. Overall the work supports the use of phytoremediation as a potential remedial option for soils contaminated with mixed contaminants.